Congenital absence of superior vena cava - case report and review of the literature - Andreea Vidru; Alexandra Cozinov; Cristina Dumitru; Andreea Avramescu; Veronica Marcu; Andra Pîrnuță; Alexandra Bouariu; Anca Panaitescu (Amaltea Medical Publishing House, 2020)
Superior vena cava (SVC) agenesis or total congenital absence of superior vena cava is a very rare vascular anomaly, mainly asymptomatic throughout neonatal period. We present a case of bilateral total congenital absence of superior vena cava and thoracic duct obstruction in a newborn which were detected during the anomaly scan at 22 weeks gestation as unilateral pleural effusion. Transthoracic echocardiography and angiography computed tomography in the postnatal period clearly established the diagnosis of congenital anomaly of the great veins. The pleural lymphatic effusion has resolved after drainage and medical treatment in 14 days.